Magnetoelastic galfenol as a stent material for wirelessly controlled degradation rates. Issue 2 (23rd March 2018) - DeRouin, Andrew; Guillory, Roger; He, Weilue; Frost, Megan; Goldman, Jeremy; Ong, Keat Ghee
Abstract: The gold standard of care for coronary artery disease, a leading cause of death for in the world, is balloon angioplasty in conjunction with stent deployment. However, implantation injuries and long‐term presence of foreign material often promotes significant luminal tissue growth, leading to a narrowing of the artery and severely restricted blood flow. A promising method to mitigate this process is the use of biodegradable metallic stents, but thus far they have either degraded too slowly (iron) or disappeared prematurely (magnesium). The present work investigates the use of a unique type of magnetic material, galfenol (iron‐gallium), for postoperative wireless control of stent degradation rates. Due to its magnetoelastic property, galfenol experiences longitudinal micron‐level elongations when exposed to applied magnetic fields, allowing generation of a microstirring effect that affect its degradation behavior. In vitro indirect cytotoxicity tests on primary rat aortic smooth muscle cells indicated that galfenol byproducts must be concentrated approximately seven times from collected 60 day degradation medium to cause ∼15% of death from all cells. Surface and cross‐sectional characterization of the material indicate that galfenol (Fe80 Ga20 ) degradation rates (∼0.55% per month) are insufficient for stenting applications. While this material may not be ideal for comprising the entire stent, there is potential for use in combination with other materials. Furthermore, the ability to control degradation rates postimplantation opens new possibilities for biodegradable stents; additional magnetoelastic materials should be investigated for use in stenting applications. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 107B: 232–241, 2019.